Even though I knew the end - Polk, C. L. (Chelsea L.) (Tordotcom, 2022)
"C. L. Polk turns their considerable powers to a fantastical noir with Even Though I Knew the End. "Stylish supernatural noir with a heart and a thrumming pulse. I devoured it."-Laini Taylor A magical detective dives into the affairs of Chicago's divine monsters to secure a future with the love of her life. This sapphic period piece will dazzle anyone looking for mystery, intrigue, romance, magic, or all of the above. An exiled augur who sold her soul to save her brother's life is offered one last job before serving an eternity in hell. When she turns it down, her client sweetens the pot by offering up the one payment she can't resist-the chance to have a future where she grows old with the woman she loves. To succeed, she is given three days to track down the White City Vampire, Chicago's most notorious serial killer. If she fails, only hell and heartbreak await"--